ANALISIS KETERKAITAN ANTARA KOMPETENSI SUMBER DAYA MANUSIA, PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH, KOMPETENSI STAFF DAN KUALITAS LAPORAN KEUANGAN DAERAH (Studi Empiris Kecamatan Banjarsari Surakarta) - LMS Kristiyanti; Timur Angin Prasetyo Putri; Desy Nur Pratiwi (Jurnal Akuntansi dan Pajak, 2024)
This study aims to examine the effect of human resource competence, application of regional financial accounting systems and staff competence on the quality of regional financial reports. The research sample used was staff working in the Banjarsari sub- district in Surakarta City. The sampling method used purposive sampling method. With the method of data analysis using multiple regression analysis with a significance level of 5 percent, which was processed using the Statistical Package for Social Science (SPSS) Version 23 program. The results of this study indicate that the Competence of Human Resources does not affect the Quality of Financial Statements while the Application of the Regional Financial Accounting System and Staff Competence influences the Quality of Financial Statements.